Redes de sensores sem fio aplicadas à aquisição de dados de solos. - MELO, Érico Castro de Albuquerque. (2019)
Sanitary landfills are sites of controlled disposal of municipal solid waste, designed to minimize the environmental impacts caused by the liquids and gases resulting from the decomposition of organic matter present in the waste. One of these gases is methane, which is a greenhouse gas. In this work, a data acquisition system based on wireless sensor networks is proposed to monitor the levels of methane in a landfill. The sensor node is designed to measure temperature, relative humidity and methane concentration. Communication between the network nodes is based on the IEEE 802.15.4 standard. The proposed system allows for continuous monitoring of methane emissions and reduces the exposure of workers to the hazardous environmental conditions of a landfill. A prototype sensor node was developed and tested in the laboratory as a demonstration of the feasibility of the system. Based on the obtained results, it was verified that the system is capable of monitoring environmental variables via wireless network, thus contributing to the modernization of environmental monitoring methods employed in landfills.